2018
DOI: 10.1016/j.ebiom.2018.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Day-Night Oscillation of Atrogin1 and Timing-Dependent Preventive Effect of Weight-Bearing on Muscle Atrophy

Abstract: BackgroundAtrogin1, which is one of the key genes for the promotion of muscle atrophy, exhibits day-night variation. However, its mechanism and the role of its day-night variation are largely unknown in a muscle atrophic context.MethodsThe mice were induced a muscle atrophy by hindlimb-unloading (HU). To examine a role of circadian clock, Wild-type (WT) and Clock mutant mice were used. To test the effects of a neuronal effects, an unilateral ablation of sciatic nerve was performed in HU mice. To test a timing-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Since TFs of these genes form core clock components in circadian rhythm mechanisms [ 31 ], these clock genes could play a role as key regulators associated with underlying mechanisms of physiology and metabolism under spaceflight [ 18 , 52 ]. For example, previous studies showed that clock genes have demonstrated a role of circadian rhythm in muscle atrophy and bone remodeling [ 53 , 54 , 55 ]. In addition, these clock genes have been implicated in NAFLD [ 56 ], the symptoms of which have been observed in mice during spaceflight [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since TFs of these genes form core clock components in circadian rhythm mechanisms [ 31 ], these clock genes could play a role as key regulators associated with underlying mechanisms of physiology and metabolism under spaceflight [ 18 , 52 ]. For example, previous studies showed that clock genes have demonstrated a role of circadian rhythm in muscle atrophy and bone remodeling [ 53 , 54 , 55 ]. In addition, these clock genes have been implicated in NAFLD [ 56 ], the symptoms of which have been observed in mice during spaceflight [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its mechanism remains unclear. In a recent animal study, it was reported that the preventive effects of stimulus like a rehabilitation on muscle atrophy depended on its timing (124). Intermittent weight-bearing for 4 h prevents the hindlimb-unloading-induced muscle atrophy and the up-regulation of Atrogin1 expression, which is one of the muscle catabolic genes (124,125).…”
Section: Muscle Sizementioning
confidence: 99%
“…In a recent animal study, it was reported that the preventive effects of stimulus like a rehabilitation on muscle atrophy depended on its timing (124). Intermittent weight-bearing for 4 h prevents the hindlimb-unloading-induced muscle atrophy and the up-regulation of Atrogin1 expression, which is one of the muscle catabolic genes (124,125). These preventive effects are greater in mice, which perform weightbearing in the early active phase compared with weight-bearing in the late period of active phase (equivalent to evening in human because mice are nocturnal) (124).…”
Section: Muscle Sizementioning
confidence: 99%
See 2 more Smart Citations